Attitude to the Menopause and Sex amongst Middle-Aged Women in a Family Medicine Clinic in Ibadan, Nigeria - Folasade Adenike Bello; Olufunmilola Olutosin Daramola (Obstetrics and Gynecology International)
Background. Menopause is the expected end of reproductive life. Having a positive attitude towards it has been shown to result in a positive experience, while a negative attitude is associated with negative experiences and symptoms. Traditionally, women often abstain from sex after menopause. The study aimed to determine the level of awareness and perceptions about the menopause and sex in perimenopausal women attending a general outpatient clinic. Methods. Women over 40 years were recruited from the Family Medicine Department of University College Hospital, excluding those who were menopausal. Data analyses were done with chi-square test (p<0.05). Results. Most (302; 86.4%) of the 352 surveyed participants were aware of the menopause. Only 36.1% anticipated associated symptoms. About half (55.7%) were indifferent to menopause onset, while 23% had a positive attitude and 21.4% had a negative attitude, respectively. Younger women were less likely to have a positive attitude to the menopause (p=0.04). There were negative cultural beliefs towards sex. Sexual activity was low and declined with age (p<0.001). Many women would like treatment to improve their sexual activity. Conclusion. Most participants had a favourable disposition towards the menopause, though sexual relationships suffer. Counselling and treatment should be offered.